OLAHRAGA SEBAGAI SARANA POLITIK DAN KEKUASAAN DALAM KEHIDUPAN SOSIAL - Hulu, Totonafo; Sinaga , Efraim Candela; Naibaho, Sandrina Malakioano; Hutasoit, Kismiati Lovita; Sebayang , Nada Misva; Yan Indra Siregar; Putra Arima (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Sport is not merely viewed as a physical activity to improve health and performance, but also plays a strategic role in social life, particularly in the fields of politics and power. This study aims to analyze the function of sport as a political and power tool in the social life of communities. The method applied is library research by analyzing various scientific sources such as journals, books, and articles related to the topic of study. Data analysis was conducted using a qualitative descriptive approach through the interpretation of various relevant literature. The research findings indicate that sport is often used as a tool for political legitimacy, a means of propaganda, and a way to create an image of power, whether by individuals, groups, or the state. On the other hand, sport also functions as an arena for social interaction that can influence the strengthening or weakening of power structures within communities. The conclusion of this study shows that sport has a strong relationship with social and political aspects, so it cannot be separated from the dynamics of power in community life.